Estimation of 2½ Dimensional Surface Structure in Kelud Volcano Region Based on Gravity Survey - M. Rahman; Sunaryo Sunaryo; Adi Susilo (Natural B, Journal of Health and Environmental Sciences, 2014)
The research in the area around Kelud Volcano based on gravity survey has been conducted in order to determine  subsurface structure and constituent composition. The research was done in July 2012 - May 2013 in the area around Kelud Volcano covered Blitar, Kediri, Wlingi, and Ngantang. In this research, the equipment that been used is gravity-meter Lacoste & Romberg type G-105. Analysis of data from field measurements performed with the followed step: calculated the correction of Bouguer anomaly, projected to the flat plane and separated regional anomaly and residual anomaly with polynomial fitting method. Interpretation was performed on three cross sections: section AB, CD, and EF. For results of cross-section AB, the values of ρ for andesite, lava, basalt and sandstone are 2.61 gr/cm3, 3.1 gr/cm3, 2.99 gr/cm3 and 1.61 gr/cm 3respectively. For cross-section CD, the values of ρ for andesite and sediment are 2.5 gr/cm3and 2.38 gr/cm3. For cross-section EF, the values of ρ for basalt, sandstone, and sediment are 2.85 gr/cm3, 1.6 gr/cm3, and 2.4 gr/cm3. From the results of models shows that basalt and andesite rocks is dominant in the region of Kelud Volcano.